2007
DOI: 10.1262/jrd.18174
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of Prolactin on Adrenal Steroid Release in Male Hatano High-Avoidance (HAA) Rats May be Mediated Through Janus Kinase 2 (Jak2) Activity

Abstract: Abstract. Prolactin (PRL) has been proposed to directly stimulate corticosterone release. However, the role of PRL on adrenocortical function in male HAA rats has not been fully clarified. The aim of this study was to investigate the effect of PRL on the secretion of corticosterone and progesterone using an in vitro cell culture system in male rats. Administration of PRL (10 -7 and 10 -6 M) resulted in dose-dependent increases in corticosterone and progesterone release. Cotreatment with PRL produced an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The whole glands were used, and the procedures were performed according to previously described methods. 9) To measure the effects of pantothenic acid on ACTH-, or PRL-stimulated release of corticosterone and progesterone, adrenal cells were pre-incubated for 24 h at 37°C in a humidified atmosphere (95% air/5% CO 2 ) with DMEM medium supplemented with 2% fetal bovine serum, 100 U/ml penicillin, and 100 mg/ml streptomycin. After 24 h in culture, the incubation medium was replaced by the same medium as previously used, and the cells were then incubated in the absence or presence of rat ACTH…”
Section: Methodsmentioning
confidence: 99%
“…The whole glands were used, and the procedures were performed according to previously described methods. 9) To measure the effects of pantothenic acid on ACTH-, or PRL-stimulated release of corticosterone and progesterone, adrenal cells were pre-incubated for 24 h at 37°C in a humidified atmosphere (95% air/5% CO 2 ) with DMEM medium supplemented with 2% fetal bovine serum, 100 U/ml penicillin, and 100 mg/ml streptomycin. After 24 h in culture, the incubation medium was replaced by the same medium as previously used, and the cells were then incubated in the absence or presence of rat ACTH…”
Section: Methodsmentioning
confidence: 99%
“…Following activation, adrenal medullary cells secrete neurotransmitters and neuropeptides such as adrenaline/noradrenaline, neuropeptide Y, vasoactive intestinal peptide, or substance P, which may, in a paracrine manner [for review see ( 180 , 181 )], influence adrenocortical CORT secretion. Moreover, neuropeptides such as prolactin and oxytocin (OXT), which are released during various types of acute stressor exposures [( 39 , 182 ); for review see ( 183 )], act as direct CORT secretagogues ( 184 186 ). Therefore, instead of rescuing ACTH signaling, it is also possible that this unknown factor is a CORT secretagogue itself, thereby simply replacing ACTH in the process of adrenal activation during heterotypic stressor exposure.…”
Section: Chronic Subordinate Colony Housingmentioning
confidence: 99%
“…Previous studies have shown that PRL receptors (PRLR) are expressed in adrenal cortex in several species (McDonough and Ewig 1982;Klemcke et al 1989;Ouhtit et al 1993;Glasow et al 1996;Glasow et al 1998). In addition to its regulatory function in the reproductive system (such as in lactation), PRL has been shown to stimulate corticosterone secretion by primary rat adrenocortical cell cultures in-vitro (Lo et al 1998;Chang et al 1999;Kau et al 1999;Lo and Wang 2002;Kan et al 2003;Lo et al 2006;Jaroenporn et al 2007). These observations led us to postulate that stress-induced PRL elevation may enhance the secretion of corticosterone in response to stress.…”
Section: Introductionmentioning
confidence: 99%